KNOWLEDGE AND SKILLS IN THE USE OF FIRE EXTINGUISHERS THROUGH FIRE FIGHTING TRAINING FOR PRINTING WORKERS PT X KARANGANYAR - Bachtiar Chahyadhi; Maria Paskanita Widjanarti; Arbi Oktavandi (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat)
In manufacturing companies, the use of production equipment and facilities has the potential and risk of hazards that can occur at any time. There were 466 cases of building and residential fires in the 2019-2024 period. To prevent and reduce the impact of fire, fire extinguishing systems such as sprinklers, fire alarms, and light fire extinguishers (APAR) are needed. Fire disasters require countermeasures through training to improve the knowledge and skills of human resources. This study aims to determine the differences in knowledge and skills in using fire extinguishers before and after training for printing workers at PT X Karanganyar. This study used an experimental design with a pre-experimental approach, using a one group pre-test post-test design. The intervention used is APAR training. The population of this study amounted to 50 respondents of PT X Karanganyar printing workers. This study used a total sampling technique with measurement of knowledge using a questionnaire and measurement of skills using a checklist. The data analysis technique used was the paired T test. The results showed that there was a significant difference in knowledge (p=0.000; p<0.05) and skills (p=0.001; p<0.05).